CONCEPTUAL SEMANTICS OF MORPHOLOGICAL CATEGORIES - Zafar Tillaev Akmalovich (Scholars Digest Publishing, 2023)
In the multifaceted classification of morphological categories, Russian in the Russian language, the verb category of the voice is included by A.V. Bondarko in co-becoming grammatical categories with predominantly interpretive semantics. In his opinion, the interpretational nature of the semantic the content of the pledge is determined by considering the linguistic meanings of an asset and a liability, the opposition of which is based on the difference personal linguistic semantic interpretation of the invariant meaning structure, including the relationship between the subject - the action - object within the framework of the interpretation of the same denotative situation.
Keywords: the verb category of the voice, noun, actual voice, article.